Exploring the Factors Behind Gen Z’s Blind Box Purchase Intention in Jakarta - Gunarian, Nathalia; Annabel, Angela; Galuh Desfianti, Winda; Angelina, Angelina (Syntax Corporation, 2025)
This research examines the psychological and social determinants affecting Generation Z's inclination to acquire blind boxes in Jakarta. The increasing popularity of blind boxes among Southeast Asian youth has led brands such as MINISO and Pop Mart to engage Generation Z through elements of surprise, collectability, and emotional connection. This study utilises a quantitative methodology through Structural Equation Modelling (SEM) to examine the impact of social value, perceived uncertainty, and emotional responses on purchase intention. Data were gathered via an online questionnaire disseminated to Gen Z consumers in Jakarta who often purchase blind boxes. The findings indicate that social value, influenced by peer pressure and social media exposure, significantly enhances purchase intention. Emotional responses, including excitement and satisfaction, moderate the relationship between collection value and intention. Nevertheless, perceived ambiguity does not substantially influence intention via emotional responses. These data indicate that Generation Z acquires blind boxes more for emotional gratification and social inclusion rather than for the excitement of uncertainty. The research provides guidance for marketers to develop ethical methods that resonate with Gen Z's emotional and social requirements while reducing the likelihood of impulsive or compulsive purchasing behaviours